DEM of triaxial tests on crushable cemented sand - de Bono, John P.; McDowell, Glenn R.; Wanatowski, Dariusz (Springer Verlag, 2014)
Using the discrete element method, triaxial simulations of cemented sand consisting of crushable particles are presented. The triaxial model used features a flexible membrane, allowing realistic deformation to occur, and cementation is modelled using inter-particle bonds. The effects of particle crushing are explored, as is the influence of cementation on the behaviour of the soil. An insight to the effects that cementation has on the degree of crushing is presented.